Respon Tanaman Kacang-Kacangan yang Bersifat Determinate dan Indeterminate pada Berbagai Kondisi Ketersediaan Air - , Thomas; M. J. Robertson; S. Fukai (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2003)
Growth and yield of soybean and blackgram, having determinate and indeterminate in flowering respectively, were compared under three water regimes. Under well-watered conditions, blackgram continuously produces flowers where under rainfed + irrigation and rainfed condition, two periods of flowering can be distinguished. While only one period of flowering was observed in soybean. The second flush of flowering of blackgram in rainfed and rainfed + irrigation areas occurred during high rain fall. Partial irrigation as much as 80 mm toward the end of pod filling in soybean did not give benefit to soybean, but irrigation stimulate flowering in blackgram and increase yield up to 25%. Thus indeterminate behavior might give higher yield under rainfed condition due to its flexibility of flowering. Key words: Determinate, Indeterminate, Flowering, Water stress